Gluten-free pancakes and waffles prepared from Riceberry flour instant mix with xanthan gum addition: physical, sensory and chemical properties - Phongnarisorn, Benjapor; Pichaiyut, Nattayawan; Tongkaew, Patthamawadee (Agriculture and Natural Resources, 2023)
Importance of the work: Pancakes and waffles are popular breakfast and dessert items commonly made from wheat flour containing gluten. Riceberry flour has the potential to be used to create gluten-free baked products. However, the lack of the gluten structure influences the quality of waffles and pancakes. Objectives: To investigate the effect of xanthan gum on the quality of gluten-free waffles and pancakes made from Riceberry flour. Materials & Methods: Physical quality measurements were made of the pancake spread ratio, the percentage weight loss during cooking and the color. Sample texture was measured using a CT-3 Brookfield texture analyzer. The sensory acceptability was conducted using a 9-point hedonic scale. The moisture content and water activity of all samples were measured. Results: Xanthan gum addition resulted in decreases in the percentage weight loss during cooking and in the spread ratio of the pancakes. The pancake shear force decreased with xanthan gum addition (0.25–1%). Furthermore, this addition decreased the hardness, chewiness and gumminess of the waffles, while increasing their springiness. Waffles and pancakes with 0.5% added xanthan gum received the highest acceptable scores that were significantly higher than the control samples. Main finding: The optimum amount of xanthan gum addition to improve the quality of gluten-free waffles and pancakes made from Riceberry flour was 0.5%. This addition retained more moisture in the products than the control and provided a viscoelastic network that mimicked gluten in the final products.